37 INVENTARISASI PENGGUNAAN LAHAN HUTAN PADA KAWASAN HUTAN KONSERVASI DI SUAKA MARGASATWA BENTAYAN PADA WILAYAH DESA BEJI MULYO KECAMATAN TUNGKAL JAYA KABUPATEN MUSI BANYUASIN - Syofian, Dedy; Abubakar, Rafeah; Yuningsih, Lulu (Sylva : Jurnal Penelitian Ilmu-Ilmu Kehutanan, 2014)
This study aims to determine the total area of the Bentayan Wildlife land use rather than as a conservation forest area, know the different types of land use in the region Bentayan Wildlife and find out the reason the public or others in the areas of land use Bentayan Wildlife as a business unit. The data collection was conducted in August to September 2013.The method used is that known location survey research, while collecting data through observation and interviews directly to KK example, the method of result through descriptive analysis with qualitative and quantitative approaches that explain or describe what it is according to the conditions that exist in the field.From well known results in the use of forest land Forest Wildlife Conservation Bentayan of 50 families in the form of examples is 201.8 ha rubber plantation area of 131.1 ha, 60.7 ha of oil palm plantations and citrus orchards 10 Ha. From the vast number, the rubber plant business type selected Mulyo Beji village community forest land conservation use. While the economy as a reason to make a living day-to-day village of Beji Mulyo encourage people to use forest land Bentayan Wildlife Conservation in District Tungkal Jaya Regency of Musi Banyuasin.